A personal leadership statement (2023)
We see ourselves as individuals who focus on creating realistic changes in others that are helpful for everyone. A leader will guide others towards a common objective, hear their opinions and motivate them to achieve their full potential, academically and personally. A teacher-leader fosters a positive learning environment that encourages open communication, collaboration, and creativity, someone who inspires confidence and provides confidence to their followers. We are committed to providing equal opportunities for all students, recognizing and addressing individual strengths and challenges. We also serve as mentors, providing guidance, support, and building their teaching skills with colleagues. They continuously seek out professional development opportunities to improve their own knowledge and abilities.